(untitled) (Journal of Engineering Science, 2021)
Social license to operate is a measure to engage with and gain acceptance from the stakeholders for large infrastructure projects. The object of this study is to measure social license to operate an infrastructure project in Khulna city, Bangladesh. Predicated on an established model, 16 statements were selected as the basis for measuring the social license to operate. A questionnaire survey was conducted among 44 local stakeholders. Using varimax rotation, five different components were identified: socio-political, economic, procedural fairness, interactional trust, and institutional trust. The model was statistically tested and found to be a medium fit explaining the results. The findings are that the project has gained socio-political, economic, procedural fairness, and interactional trust of the stakeholders, yet lacks institutional trust factor to achieve a social license to operate. The paper recommends the inclusion of the social license to operate concept in infrastructure planning and implementation phases in Bangladesh. Journal of Engineering Science 12(2), 2021, 1-10